The building performance of old and new KTMB quarters in relation to bylaws / Mohd Nurhafifi Shaari - Shaari, Mohd Nurhafifi (2008)
The definition of building maintenance suggested by the DOE Committee runs as follows; 'Building Maintenance is work undertaken in order to keep, restore or improve every facility, i.e. every part of a building, its services and surrounds, to currently acceptable standard and to sustain the utility and value of the facility.' The difficulty with housing maintenance in the public sector is that although there may be general agreement that housing should be kept 'in a good state of repair', when it comes to actual repairs, there is very reason to expert different priorities being emphasized by tenants, housing managers, maintenance engineers, surveyors, foremen and maintenance operatives themselves. Tenants, for example, are likely to be most concerned with those repairs that affect them personally, causing inconvenience, discomfort or just unsightliness and they naturally want the repairs completed as quickly as possible.